Transformative Urban Experimentation: Reimagining the Governance of Cities Towards Sustainability - Sharp, Darren Alexander Guttman (Curtin University, 2018)
This thesis by publication used action research to build capacity for grassroots agency and evaluate the direct impacts of urban experimentation from the perspective of participants in an urban living lab and investigated enabling processes of transformation through multiple case studies across a variety of socio-institutional contexts. This thesis developed an agency-centred analysis of urban experimentation to interpret how social learning, institutional arrangements, dynamics of transformation and capture and new urban imaginaries can drive the transformation of cities towards sustainability.